Repurposing the psoriasis drug Oxarol to an ointment adjuvant for the influenza vaccine. (15th February 2020) - Sato, Ryota; Makino-Okamura, Chieko; Lin, Quingshun; Wang, Muying; Shoemaker, Jason E; Kurosaki, Tomohiro; Fukuyama, Hidehiro
Abstract: Aluminum precipitates have long been used as adjuvants for human vaccines, but there is a clear need for safer and more effective adjuvants. Here we report in a mouse model that the psoriasis drug Oxarol ointment is a highly effective vaccine adjuvant. By applying Oxarol ointment onto skin, humoral responses and germinal center (GC) reactions were augmented, and the treated mice were protected from death caused by influenza virus infection. Keratinocyte-specific vitamin D3 receptor ( Vdr ) gene expression was required for these responses through induction of the thymic stromal lymphopoietin ( Tslp ) gene. Experiments involving administration of recombinant TSLP or, conversely, anti-TSLP antibody demonstrated that TSLP plays a key role in the GC reactions. Furthermore, cell-type-specific Tslpr gene deletion or diphtheria toxin-mediated deletion of specific cell types revealed that CD11c + cells excluding Langerhans cells were responsible for the Oxarol-mediated GC reactions. These results indicate that active vitamin D3 is able to enhance the humoral response via Tslp induction in the skin and serves as a new vaccine adjuvant. Abstract : Transdermal Oxarol is an adjuvant for influenza vaccination